Sharing on Facebook and Face-to-Face What Others Do or Approve: Word-of-Mouth Driven by Social Norms - Zhang, Mingyue; Lu, Jingyi; Hallman, William K. (Frontiers in Psychology, 2021)
Information sharing on social media (i.e., electronic word-of-mouth, eWOM) and face-to-face (fWOM) plays an important role in message dissemination. The current research investigates the effectiveness of group norms in motivating eWOM and fWOM. Drawing upon the psychological distance and construal level literature, the current research tests the impact of group norms, the interaction effect of norms type (descriptive vs. injunctive norms), and group distance on eWOM and fWOM. Based on one field study and three lab experiments, the current research finds that normative cues in messages are impactful in driving WOM and the impact becomes especially stronger when the psychological distance of the social group is congruent with that of norms type tied to the group. Specifically, an interaction effect emerges: distant (close) group injunctive (descriptive) norms are more impactful in driving WOM than close (distant) group injunctive (descriptive) norms. Contrary to the conventional wisdom that a close group has greater impacts than distant groups in terms of social influence, the current research shows that messages with distant groups are more (or at least equally) likely to be shared than with a close group when tied with injunctive norms. The findings suggest that group norms are perceived to be more relevant when there is a match between the psychological distance of the social group and the norms type tied to the group.